2018
DOI: 10.6007/ijarbss/v8-i3/3951
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Factors and Organizational Performance: A Resource-Based view and Social Exchange Theory Viewpoint

Abstract: To compete with the market challenges, organizations including the banking organizations are concerned to enhance their organizational performance. Considering this phenomenon, this study proposes the conceptual framework representing the organizational factors namely, strategic orientation, organizational culture and organizational commitment influencing the organizational performance. Overall, five research propositions have been framed grounded on the relevant review of the pertinent literature and focused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 83 publications
2
36
0
2
Order By: Relevance
“…Serrasqueiro et al (2018) identified some critical capabilities in the area of cost estimation, environmental scanning, assessment, and predictions, work definitions, clients' criteria as well as work objectives as the major variables of success. Others are; prompt product/service delivery Bocconcelli et al (2018) management knowledge and skills, business processes, evaluation of performance, business structure and systems (Ahmed et al, 2018;Wang and Zhou, 2019) business plan, (Arasa and K'Obonyo, 2012;Forth and Bryson, 2019;Ighodalo et al, 2019) managerial attitude and practices (Asikhia, 2010;Okwachi et al, 2013;Sabli and Latiff, 2019), strategy (Maney et al, 2014;Rizan, Balfas, and Purwohedi, 2019) and marketing (Omar and Anas, 2014;Van Scheers, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Serrasqueiro et al (2018) identified some critical capabilities in the area of cost estimation, environmental scanning, assessment, and predictions, work definitions, clients' criteria as well as work objectives as the major variables of success. Others are; prompt product/service delivery Bocconcelli et al (2018) management knowledge and skills, business processes, evaluation of performance, business structure and systems (Ahmed et al, 2018;Wang and Zhou, 2019) business plan, (Arasa and K'Obonyo, 2012;Forth and Bryson, 2019;Ighodalo et al, 2019) managerial attitude and practices (Asikhia, 2010;Okwachi et al, 2013;Sabli and Latiff, 2019), strategy (Maney et al, 2014;Rizan, Balfas, and Purwohedi, 2019) and marketing (Omar and Anas, 2014;Van Scheers, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Business management is nowadays increasingly emphasizing the importance of knowledge assets included competency (Astuti et al, 2020). Rohana and Abdullah (2017) revealed that there is a significant relationship between leadership performance, spedifically leadership competence on organizational performance (Ahmed et al, 2018). The leadership is a key competence in management during an economic crisis and a community crisis (Sparl, 2013), therefore managerial competence has a dominant influence on organizational performance (Zaim et al, 2013;Faisal, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are certain parameters which are expected to affect workforces' performance positively/negatively (Naseem et al, 2012). Therefore, organizational culture, organizational justice, organizational politics and psychological empowerment are considered as dynamic forces which affect the employees' performances (Ahmed et al, 2018). These variables have been researched in diverse contexts including the higher educational institutions with diverse results/outcomes and the same significant results are expected from the empirical investigation in the current study.…”
Section: Literature Reviewmentioning
confidence: 75%